Sero-prevalence and factors associated with anti-Brucella antibodies in slaughter livestock in Uganda - Bugeza, James; Roesel, Kristina; Moriyon, Ignacio; Mugizi, Denis; Alinaitwe, Lordrick; Kivali, Velma; Kankya, Clovice; Cook, Elizabeth Anne Jessie (Frontiers in Epidemiology, 2023)
Brucellosis is endemic in Uganda and is a major cause of production losses in livestock. Early detection and quantification of the disease is vital for its control and eradication. The aim of this study was to assess the sero-prevalence and factors associated with anti-Brucella antibodies in slaughtered livestock. Sera from 886 cattle, 925 small ruminants, and 900 pigs were collected from regional abattoirs in Northern, Eastern and Central Uganda. To estimate sero-prevalence, sera were serially tested using a combination of the Rose Bengal Test (RBT) and Native Hapten (NH) immunoprecipitation test. True sero-prevalence was estimated using the Rogan-Gladden estimator considering the sensitivity and specificity of the NH immunoprecipitation test. Multivariable logistic regression was used to assess factors associated with seropositivity for anti-Brucella antibodies. Small ruminants showed the highest seroprevalence (6.7%, 95%CI=4.2 -7.1) followed by cattle (3.8%, 95%CI=2.4-4.9) and pigs (2.8%, 95%CI=1.1-2.9). Seropositivity for anti-Brucella antibodies was associated with region of origin (OR=4.6,95%CI=1.49-17.75, p=0.013) for cattle; sex (OR=2.90, 95%CI=1.5-6.34, p=0.004), age (OR=4.04, CI=1.07-8.52, p=0.006) and species (OR=2.53, CI = 1.08 -6.98) for small ruminants; and finally sex for pigs (OR=2.88, p=0.041,95%CI=1.07-8.52). Progressive control interventions must include both cattle and small ruminants since they play a bigger role in the maintenance and dissemination of Brucella. The interventions should adopt a risk-based approach with regions at higher risk being given top priority. Bacteriological and molecular studies should be undertaken to clarify the role of pigs and the goat-cattle cross infections in the epidemiological cycle of brucellosis in Uganda.